ENVIRONMENTALLY-ORIENTED COOPERATION AS AN INSTRUMENT OF SUSTAINABLE DEVELOPMENT - Urbaniec, Maria (Journal of European Economy, 2017)
In order to enhance the process of innovation in environmental industries proposed to intensify cooperation on the environment, by promoting dialogue between different sectors. The impact of cooperation on innovation and the innovation potential of enterprises, and sustainable development were proved.